2022
DOI: 10.3389/fcimb.2022.851521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Shewanella putrefaciens WS13 Biofilms Under Cold Stress

Abstract: Shewanella putrefaciens is a Gram-negative bacterium that can cause seafood spoilage under low-temperature conditions. The bacterium easily forms biofilms to enhance its survival in challenging environments. Our previous research revealed that the biofilm formed by S. putrefaciens WS13 under the low temperature (4 °C) has larger biomass and tighter structure than at an optimum growth temperature (30 °C). In this study, comparative transcriptome analysis was further performed to get insights into the global-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…S. putrefaciens has a strong biofilm-forming capability. Our group has found that the formation of biofilm of S. putrefaciens WS13 is conducive to its survival under cold stress ( 6 , 36 ). Further study found that genes such as motA, ppsA , and fabs family expressed in S. putrefaciens WS13 under 4°C help attenuate bacterial motility, enhance bacterial adhesion, and increase biofilm fluidity ( 36 , 37 ), which was beneficial for bacteria to form biofilm under cold stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. putrefaciens has a strong biofilm-forming capability. Our group has found that the formation of biofilm of S. putrefaciens WS13 is conducive to its survival under cold stress ( 6 , 36 ). Further study found that genes such as motA, ppsA , and fabs family expressed in S. putrefaciens WS13 under 4°C help attenuate bacterial motility, enhance bacterial adhesion, and increase biofilm fluidity ( 36 , 37 ), which was beneficial for bacteria to form biofilm under cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has found that the formation of biofilm of S. putrefaciens WS13 is conducive to its survival under cold stress ( 6 , 36 ). Further study found that genes such as motA, ppsA , and fabs family expressed in S. putrefaciens WS13 under 4°C help attenuate bacterial motility, enhance bacterial adhesion, and increase biofilm fluidity ( 36 , 37 ), which was beneficial for bacteria to form biofilm under cold stress. Biofilm formation began after bacteria adhered to the surface of the object, and the adhesion of bacteria was regulated by c-di-GMP ( 11 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was performed in triplicate. The 16S RNA gene was used as the reference gene for normalization 52 . The primers used (Supplementary Table 6) in the experiments were designed according to the functional gene sequence using Primer6.0.…”
Section: Weighted Gene Co-expression Network Constructionmentioning
confidence: 99%
“…As with other Gram-negative food spoilage bacteria, H. alvei uses an array of N-homoserine lactones as signaling molecules for QS [ 33 , 34 ]. Homoserine lactones (HLs) or N-acyl homoserine lactones (AHLs) are molecules commonly produced by Gram-negative bacteria, including food-borne pathogens such as bacteria of the genus Aeromonas [ 35 ], Shewanella [ 36 ], Clostridium [ 37 ], Pseudomonas [ 38 ], and Salmonella [ 39 ] among others, which constitute a cell density-dependent intercellular signaling mechanism that modulates a great variety of physiological processes, including the production of different virulence factors. Many strains of Enterobacteriaceae isolated from food are able to synthesize AHLs because these molecules are easily detectable from contaminated foods using biosensor strains or biochemical assays.…”
Section: Quorum Sensingmentioning
confidence: 99%